Two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women facing each other. The woman on the right is dressed in matching pants and top with a large corsage pinned on her left shoulder and a single flower pinned to her right shoulder. The woman on the left is dressed in a shimmery top and pants. She is facing the first woman, but she is looking at the camera. She also has a large corsage pinned to her left shoulder and a single flower pinned to her right shoulder. Her right hand is resting on the bar.